Open-hole tensile progressive damage and failure prediction of carbon fiber-reinforced PEEK–titanium laminates. (15th April 2016) - Du, Dandan; Hu, Yubing; Li, Huaguan; Liu, Cheng; Tao, Jie
Abstract: This paper studied a thermoplastic-based fiber metal laminate (FML) prepared via a hot-pressing process utilizing titanium foils, carbon fiber reinforced PEEK prepregs, and PEEK films (interface bonding layers). The open-hole tensile progressive damage and failure mechanisms were investigated by numerical and experimental methods. During the simulation, we employed three failure criterions for titanium (ductile damage), prepregs (a progressive damage in terms of strains), and interface bonding layers (cohesive model) to predict the failure of the laminates. In the experiments, the damage behavior was further verified. The open-hole tensile strength and stress–strain response agreed well with the numerical results. It was found that fiber breakage along the loading direction initiated after yield point of the laminates, following by matrix damage. When the applied load reached the ultimate value, the delamination between the titanium layer and the fiber layer propagated to the entire section, causing titanium fracture. The validated model can also be used on other notched or bolted FMLs with similar structure.